HOW IMPORTANT MARKET AND TECHNOLOGICAL ALIGNMENT IN DEVELOPING PROACTIVE DECISION-MAKING AND DESIGN FLEXIBILITIES: A SYSTEMATIC LITERATURE REVIEW - Sama, Hendi; Gabriella, Jessica; Siahaan, Mangapul (POLITEKNIK SAINS DAN TEKNOLOGI WIRATAMA MALUKU UTARA, 2026)
This systematic literature review examines how aligning market demands with technology fosters proactive decision-making. Synthesizing recent academic literature, it confirms that AI-driven analytics are crucial for shifting organizations to a proactive strategic posture, enhancing agility and forecasting. However, this transformation is hindered by significant challenges, including dependency on data quality, integration complexity, financial barriers, and ethical issues like algorithmic bias. Successful adoption requires robust risk management and the strategic integration of human oversight—encompassing critical evaluation and ethical judgment—into the data-driven process. This research provides a framework for balancing technological adoption with human-centric governance to help organizations remain competitive in the digital age. Keywords: Market and Technology Alignment, Proactive Decision-Making, Design Flexibility